2015
DOI: 10.1016/j.sleep.2015.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral JZP-110 (ADX-N05) treatment on wakefulness and sleepiness in adults with narcolepsy

Abstract: The efficacy of JZP-110 for impaired wakefulness and excessive sleepiness was observed at 150-300 mg/day and as early as one week after initiating treatment (Clinicaltrials.gov identifier NCT01485770).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 25 publications
4
54
0
Order By: Relevance
“…The overall safety and tolerability in this study were consistent with other studies of solriamfetol, with the most common adverse events being headache, nausea, decreased appetite, nasopharyngitis, dry mouth, and anxiety; no serious adverse events were reported. Additionally, small increases in mean blood pressure and heart rate were observed, as previously reported with other wake‐promoting agents and psychostimulants …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The overall safety and tolerability in this study were consistent with other studies of solriamfetol, with the most common adverse events being headache, nausea, decreased appetite, nasopharyngitis, dry mouth, and anxiety; no serious adverse events were reported. Additionally, small increases in mean blood pressure and heart rate were observed, as previously reported with other wake‐promoting agents and psychostimulants …”
Section: Discussionsupporting
confidence: 88%
“…This sample size was based on an estimate of 54 patients per group to provide at least 80% power to detect a difference of 6 minutes in the mean sleep latency time as determined from the MWT (mean of the first 4 trials) and a difference of 4 points on the ESS changes from baseline to week 12 between each solriamfetol treatment dose group and placebo. These estimates were based on the effects observed at the 150 and 300 mg doses in 2 phase 2 studies . This calculation also assumed standard deviations (SDs) in the changes from baseline of 10 minutes for the MWT and 6 points for the ESS, and a 2‐sided significance level of 0.05 using a t test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 4 weeks of JZP-110 at doses of 150 mg (weeks 1, 3) and 300 mg (weeks 2, 4), ESS decreased –6.7 in the treatment group (n=33) compared to –2.4 in the placebo group (n=33). MWT (40-minute test) mean-sleep-latency (MWT SL) after 2 weeks at the 300 mg dose was 12.7±10.6 minutes longer compared to placebo results of 0.9±6.0 minutes 50. A parallel group trial using 150 mg × 4 weeks and 300 mg × 8 weeks showed significant improvements in MWT SL, ESS, and CGIC in treated patients (n=44) compared to placebo (n=49).…”
Section: New Developments and Future Therapiesmentioning
confidence: 91%
“…It does not release monoamines nor does it inhibit serotonin reuptake; it also does not inhibit MAO-A enzymatic activity 50. In randomized, double-blind, placebo-controlled clinical trials, JZP-110 underwent Phase II (NCT01485770)50 and Phase II B (NCT01681121)51 testing in adults with narcolepsy with and without cataplexy 50,51. After 4 weeks of JZP-110 at doses of 150 mg (weeks 1, 3) and 300 mg (weeks 2, 4), ESS decreased –6.7 in the treatment group (n=33) compared to –2.4 in the placebo group (n=33).…”
Section: New Developments and Future Therapiesmentioning
confidence: 99%